Les homosexuels masculins et leurs « mondes » [1965] - Evelyn Hooker (Genre, Sexualité et Société)
In this article, the author proposes a synthesis of both her previous work and the literature in psychology she intends to argue against. She emphasizes the social dimension of homosexual experience, most often ignored by psychologists. From the results of an ethnographic study and interviews, she describes how homosexuals in Los Angeles are part of a plurality of social "worlds," including "gay" bars, already very numerous at this time despite recurring problems that oppose the homosexual community to public authorities and law enforcement.